2013
DOI: 10.1200/jco.2013.31.15_suppl.2559
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of GBS-01 for advanced pancreatic cancer refractory to gemcitabine.

Abstract: 2559 Background: Arctigenin, which is abundant in the seeds of Arctium lappa Linné, was found by a novel strategy to attenuate cancer cells’ tolerance to glucose deprivation (antiausterity) and showed antitumor activity in mouse xenograft models. GBS-01 is an orally administered drug and contains rich arctigenin extracted from Arctium lappa Linné, which is one of the traditional herbal medicine. This study investigated the maximum-tolerated dose of GBS-01 based on the frequency of dose-limiting toxicities (DL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The pharmacokinetic profile of AR in humans after oral administration was investigated in a phase I clinical trial of the herbal product GBS-01. After oral administration of GBS-01 at a dose of 12 g AR per person, the peak concentration of AR in the plasma of the pancreatic cancer patients was 66.56±26.81 ng/mL, and the AUC was 487.97±368.86 ng*h/mL [75] . Given the low molecular weight of AR and its high permeability demonstrated in the absorption models, the poor oral bioavailability of AR should be mainly due to its extensive first-pass metabolism rather than limita-www.nature.com/aps Gao Q et al tions of membrane permeability.…”
Section: Rat Intestinal Contentmentioning
confidence: 97%
See 1 more Smart Citation
“…The pharmacokinetic profile of AR in humans after oral administration was investigated in a phase I clinical trial of the herbal product GBS-01. After oral administration of GBS-01 at a dose of 12 g AR per person, the peak concentration of AR in the plasma of the pancreatic cancer patients was 66.56±26.81 ng/mL, and the AUC was 487.97±368.86 ng*h/mL [75] . Given the low molecular weight of AR and its high permeability demonstrated in the absorption models, the poor oral bioavailability of AR should be mainly due to its extensive first-pass metabolism rather than limita-www.nature.com/aps Gao Q et al tions of membrane permeability.…”
Section: Rat Intestinal Contentmentioning
confidence: 97%
“…The hydrolysis of AR was mediated by human paraoxonase 1 in plasma [73] , and glucuronidation of AR was mediated by UGT1A9, UGT2B7 and UGT2B17 in the liver and intestine [74] . A phase I clinical trial of the herbal product GBS-01 on pancreatic cancer patients demonstrated that after oral administration of GBS-01 at a dose of 12 g AR per person, the area under the plasma concentration versus time curve (AUC) of arctigenin-glucuronide was almost 1000 times higher than that of AR [75] . Notably, the extent of metabolism of AR might be different between species.…”
Section: Pharmacokinetic Properties Of Armentioning
confidence: 99%
“…Thus, selectively targeting metabolically stressed (glucose-deprived) tumor cells, including PEL, may represent a promising strategy with which to inhibit tumor cell proliferation without affecting normal cells. In this regard, arctigenin has been shown to preferentially induce tumor growth suppression and apoptosis in glucose-deprived tumor cells (34)(35)(36). In this study, we examined a novel biological function of arctigenin and the molecular mechanisms through which it preferentially induces the apoptosis of glucosestarved PEL cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to affecting cell signaling, arctigenin influences ER stress and inhibits or activates the UPR, resulting in apoptosis or protection against ER stress (28)(29)(30). Arctigenin has been shown to exhibit anticancer activity in numerous types of cancer, including hepatocellular carcinoma (23), colon cancer (25), gastric cancer (31), pancreatic cancer (32), gallbladder cancer (27), breast cancer (24,26), ovarian cancer (33) and pancreatic cancer (34,35). One of the interesting anticancer properties of arctigenin is that it can preferentially induce the apoptosis of cancer cells under conditions of glucose starvation (34,36).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation